1995
DOI: 10.1016/0896-6273(95)90179-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation in GABA mini amplitude is the consequence of variation in transmitter concentration

Abstract: Miniature postsynaptic currents (minis) in cultured retinal amacrine cells, as in other central neurons, show large variations in amplitude. To understand the origin of this variability, we have exploited a novel form of synapse in which pre- and postsynaptic receptors sample the same quantum of transmitter. At these synapses, mini amplitudes measured simultaneously in the 2 cells show a strong correlation, accounting for, on average, more than half of the variance in amplitude. Two pieces of evidence support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(166 citation statements)
references
References 37 publications
12
153
1
Order By: Relevance
“…This suggests that activity blockade may induce a coordinated set of presynaptic and postsynaptic changes at inhibitory synapses. In support, previous evidence demonstrated that variations in both the GABA content of vesicles (Frerking et al, 1995) and the number of postsynaptic GABA A receptors (Nusser et al, 1997(Nusser et al, , 1998 determine mIPSC amplitude. Moreover, a reduction in both the staining intensity of GAD-65 and synaptic GABA A receptors was previously observed in cultured cortical neurons after activity blockade (Kilman et al, 2002).…”
Section: Activity-dependent Scaling Of Gabaergic Synapse Strengthsupporting
confidence: 84%
“…This suggests that activity blockade may induce a coordinated set of presynaptic and postsynaptic changes at inhibitory synapses. In support, previous evidence demonstrated that variations in both the GABA content of vesicles (Frerking et al, 1995) and the number of postsynaptic GABA A receptors (Nusser et al, 1997(Nusser et al, , 1998 determine mIPSC amplitude. Moreover, a reduction in both the staining intensity of GAD-65 and synaptic GABA A receptors was previously observed in cultured cortical neurons after activity blockade (Kilman et al, 2002).…”
Section: Activity-dependent Scaling Of Gabaergic Synapse Strengthsupporting
confidence: 84%
“…Furthermore, the functional properties of synaptic and extrasynaptic GABA A receptors could differ (Somogyi, 1989). On the other hand, the finding that patch responses induced by low micromolar concentrations of GABA have a faster decay [Jones and Westbrook (1995) and this study] closer to that of the mIPSCs (see Table 1) could be consistent with the proposal that synaptic GABA transients occur in such a low range (Frerking et al, 1995). It should be noted, however, that the concentration of GABA in synaptic vesicles is high (Burger et al, 1991); therefore, its peak cleft concentration could reach the hundreds of micromolar to millimolar range.…”
Section: Comparison Between Mipscs and Patch Responses To Brief Pulsesupporting
confidence: 73%
“…Thus we could predict that the concentration of GABA necessary for saturation could be very high, raising the possibility that neocortical GABA A receptors may not be saturated during synaptic transmission. In "dinapses" of amacrine cells it has been suggested that GABA A receptors are not saturated, based on the observation that transmitter concentration is the major determinant of mIPSC amplitude (Frerking et al, 1995). On the other hand, the low quantal variance of evoked IPSCs (Edwards et al, 1990), nonstationary fluctuation analysis, and pharmacological approaches support the hypothesis of saturation in hippocampal granule cells (Otis and Mody, 1992;De Koninck and Mody, 1994).…”
Section: Functional Implicationsmentioning
confidence: 76%
“…Indeed, it was elegantly demonstrated that the variability in mEPSC amplitude mediated by AMPARs at putative single hippocampal synapses is caused by fluctuations in the glutamate concentration in the synaptic cleft (11). Similarly, it is also likely that the large variability in ␥-aminobutyric acid (GABA) receptor-mediated miniature inhibitory postsynaptic current amplitude in amacrine cells is caused by fluctuations in the amount of GABA in each quantum, although it remains formally possible that changes in the numbers or properties of GABA receptors could contribute (30). Recently, two additional laboratories have reported large fluctuations in the amount of NMDAR-mediated calcium influx from release to release and have provided compelling evidence that NMDARs on hippocampal neurons are also unlikely to be saturated by quantal release (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Based on an estimated CV of synaptic vesicle diameters of 11-13%, synaptic vesicle volumes at hippocampal synapses may vary by 40% (7,31). The amount of glutamate packaged in single vesicles will vary by the third power of the vesicle diameter (7,30). Second, clearance of glutamate from the synaptic cleft may vary from release to release (refs.…”
Section: Discussionmentioning
confidence: 99%